GHR1 Zircon – A New Eocene Natural Reference Material for Microbeam U‐Pb Geochronology and Hf Isotopic Analysis of Zircon. Issue 1 (26th December 2018) - Eddy, Michael P.; Ibañez‐Mejia, Mauricio; Burgess, Seth D.; Coble, Matthew A.; Cordani, Umberto G.; DesOrmeau, Joel; Gehrels, George E.; Li, Xianhua; MacLennan, Scott; Pecha, Mark; Sato, Kei; Schoene, Blair; et al.
Abstract : We present multitechnique U‐Pb geochronology and Hf isotopic data from zircon separated from rapakivi biotite granite within the Eocene Golden Horn batholith in Washington, USA. A weighted mean of twenty‐five Th‐corrected 206 Pb/ 238 U zircon dates produced at two independent laboratories using chemical abrasion‐isotope dilution‐thermal ionisation mass spectrometry (CA‐ID‐TIMS) is 48.106 ± 0.023 Ma (2 s analytical including tracer uncertainties, MSWD = 1.53) and is our recommended date for GHR1 zircon. Microbeam 206 Pb/ 238 U dates from laser ablation‐inductively coupled plasma‐mass spectrometry (LA‐ICP‐MS) and secondary ion mass spectrometry (SIMS) laboratories are reproducible and in agreement with the CA‐ID‐TIMS date to within < 1.5%. Solution multi‐collector ICP‐MS (MC‐ICP‐MS) measurements of Hf isotopes from chemically purified aliquots of GHR1 yield a mean 176 Hf/ 177 Hf of 0.283050 ± 17 (2 s, n = 10), corresponding to a εHf0 of +9.3. Hafnium isotopic measurements from two LA‐ICP‐MS laboratories are in agreement with the solution MC‐ICP‐MS value. The reproducibility of 206 Pb/ 238 U and 176 Hf/ 177 Hf ratios from GHR1 zircon across a variety of measurement techniques demonstrates their homogeneity in most grains. Additionally, the effectively limitless reserves of GHR1 material from an accessible exposure suggest that GHR1 can provide a useful reference material for U‐Pb geochronology of Cenozoic zircon and Hf isotopic measurements of zircon with radiogenic 176 Hf/ 177 Hf. Key Points: We suggest a new Eocene zircon reference material, GHR1. U‐Pb and Hf isotopic systematics in GHR1 zircon are homogeneous with a 206 Pb/ 238 U date of 48.106 +/‐ 0.023 Ma (2 s ) and a 176Hf/177Hf of 0.283050 +/‐ 17 (2 s ). GHR1 fulfills a need for abundant and easily available Cenozoic zircon reference materials.